Myostatin (GDF-8) Inhibits Chondrogenesis and Chondrocyte Proliferation In Vitro by Suppressing Sox-9 Expression - Elkasrawy, Moataz (2011)
Here, we investigate a possible direct role for myostatin in chondrogenesis. First, we examined the effects of myostatin on the proliferation of bone marrow stromal cells (BMSCs) and epiphyseal growth plate (EGP) chondrocytes isolated from myostatin-deficient mice. Results show that myostatin deficiency is associated with a significant (P<.001) increase in proliferation of both BMSCs (+25%) and EGP chondrocytes (+35%) compared to wild-type cells. Next, we examined the effects of myostatin treatment on chondrogenic differentiation of bone marrow-derived mesenchymal stem cells (BMSC). These experiments show that myostatin treatment starting at either 0 or 48 hrs induces a significant decrease in Col2 protein synthesis by 31% (P<0.001) and 25% (P<0.05), respectively. Real-time PCR reveals significant (P<.01) down regulation of Sox9 mRNA expression with 10- and 100ng/ml treatments. Together, these findings suggest that myostatin has direct effects on chondrogenesis, and may therefore represent a potential therapeutic target for improving bone repair.